Non-fatal occupational fall and slip injuries among commercial fishermen analyzed by use of the NOMESCO injury registration system - Jensen, Olaf C. (American journal of industrial medicine, 2000)
Background Fall injuries constitute a significant problem in commercial fishing and such injuries have hitherto not been the subject of closer analysis. Methods The distribution and the characteristics of 582 occupational injuries among commercial fishermen are described by using data from an emergency department for the period 1990–1997, recorded in a special registration system. Results Consistent with other investigations, injuries from falls made up 25% of all injuries; they were the cause of 28% of all contusions, 32% of all fractures, 61% of all sprains and strains, 40% of all injuries to lower extremities, and 62% of all injuries to the chest. The proportion of fall injuries in different age groups was U‐shaped and constitutes around 40% for men both under 20 years and over 50 years of age, and around 20% for those between these ages. Frequent types of injury mechanisms other than falls and slips were: getting caught (22%), contact with objects or persons (28%), foreign body (9%), and cuts (9%). Conclusions Use of proportionate data gave a detailed description of injuries from falls and slips, showing important areas for prevention. To avoid a possible misclassification of fall injuries in future studies, it is recommended to include an extra specific variable: whether falling or slipping preceded the crash phase of the injury or not. Am. J. Ind. Med. 37:637–644, 2000. © 2000 Wiley‐Liss, Inc.